Effects of pre-Ramadan education on safe Ramadan fasting of people with type 2 diabetes - Fariduddin, Md; Islam, AKM Aminul; Gaffar, Md Abu Jar; Khan, Murshed Ahamed; Alam, Md Jahangir; Hasan, Mashfiqul; Atiqur Rahman, Mohammad; Aktar, Yasmin; Sultana, Nusrat; Banu, Hurjahan; et al. (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Most of the people with uncomplicated type 2 diabetes mellitus (T2DM) fast during the holy month of Ramadan in Bangladesh. Safe Ramadan fasting is a great challenge for both physician and people with diabetes. Objectives: This study was conducted to observe the effects of Ramadan-focused structured education programs on weight, hemoglobin A1c (HbA1c), biochemical parameters and hypoglycemic episodes during Ramadan in Bangladeshi adult people with T2DM who intend to fast. Methods: This prospective study recruited 615 participants with T2DM two months before the month of Ramadan in 2014 at the Endocrinology department of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. A 2-hour structured education program was provided to 286 participants (group A) and 329 participants received the usual education provided by the treating physician (group B). All participants were followed up during and upto 1 month after Ramadan. Results: A significant reduction in the HbA1c level from pre-Ramadan to post-Ramadan was seen in both the groups (group A: 8.3±1.7%vs7.6±1.3,p<0.001; group B 8.2±1.6vs 7.7±1.4,p<0.001; mean±SD). But there were no difference of HbA1c, serum creatinine, SGPT or body weight from pre-Ramadan to post-Ramadan in either of the groups (p=ns for all). Similarly, there was no significant difference between group-A and group-B in respect of pre-Ramadan or post-Ramadan HbA1c, serum creatinine, SGPT or body weight (p=ns for all). Pre-Ramadan hypoglycemia frequency was higher in group A (51/286, 17.8%) than group B (12/329, 3.6%; p<0.001); but statistically similar hypoglycemia frequency during Ramadan was observed in both the groups (group A vs. group B: 0.3% vs. 1.8%, p=0.129). Both group A and group B participants had reduced frequency of hypoglycemia during Ramadan in comparison to those experienced 3-months prior Ramadan (p<0.001 and p=0.031 respectively) but the reduction is more marked in group A. Conclusions: Pre-Ramadan education especially when structured has significant beneficial effects on safe Ramadan fasting reflected by reduced HbA1c and hypoglycemia frequency. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2022; 1 (1): 09-14